Caracterização e propriedades do material coloidal nanoestruturado β-FeOOH/bentonita - Anaissi,Fauze Jacó (2009)
A new mixed material was obtained through the combination of the suspensions of iron oxy-hydroxide and bentonite clay, denoted BFe. Analysis of its structure (XRD, Mossbauer and TGA) and composition (AAS) suggests the maintenance of the layer structure of the clay and an increase in the thermal stability of the BFe. Electrochemical studies performed in different electrolytes show that only in an alkaline medium it is possible to observe the redox peaks relative to the processes involving Fe+2/Fe+3 pair. Tests that evaluated the potential use of the photo-Fenton process showed an efficient degradation process of the dyes in significantly reduced reaction times.